Frequency of troponin elevations in patients with influenza infection during the 2017–2018 influenza season. (March 2019) - Harris, Jesse E.; Shah, Punit J.; Korimilli, Vijay; Win, Htut
Abstract: Background: With the increased number of influenza cases observed during the 2017 – 2018 season, patients may be at a greater risk of cardiac related complications as a sequela of viral illness. We described the frequency of troponin elevations in patients with influenza infection during the 2017 – 2018 influenza season. Methods: This was a retrospective, single-center observational study. All patients aged 18 years or older and had laboratory confirmed influenza viral infection were included in the study. Troponins were considered elevated if greater than 0.3 ng/mL. Electronic health records were reviewed for demographics, laboratory values, coronary artery disease history, electrocardiography, echocardiography results, and incidence of inpatient mortality. Results: A total of 1, 131 patients had lab confirmed influenza infection. Majority of the influenza strains were influenza A, 76.2% (n = 863), and the rest of the influenza strains comprised of influenza B, 23.8% (n = 270). Thirty three (2.9%) patients had elevation of troponin levels greater than 0.3 ng/mL. Most of the patients with elevated troponin levels had influenza A infection (90.9%, n = 30), of which H3 subtype was the most common (48.5%, n = 16). Fifteen patients (45.5%) had a myocardial infarction, 20 (60.6%) had left ventricular abnormalities visualized on echocardiogram, and four (12.1%) died while inpatient. Conclusions: Our results describe the frequency of troponin elevations in patients with influenza infection at our institution during the 2017 – 2018 influenza season.